The factors related to patient safety incident reporting in inpatience in RSD Idaman Banjarbaru City - Pratiwi, Aqil Andika; Pertiwiwati, Endang; Setiawan, Herry; Wakhdi, Nanang Miftakhul; Wibowo, Hery (Media Keperawatan Indonesia, 2024)
Reported patient safety incidents are useful for identifying risks that cause harm and taking solutions to prevent the same mistakes from happening again.This study aims to find out what factors are related to reporting patient safety incidents in the inpatient room of Idaman Hospital, Banjarbaru City. This research is quantitative research with a descriptive correlation design and cross-sectional approach. 128 nurses in the inpatient room of Banjarbaru City Ideal Hospital used the questionnaire.The results of the study showed that there was no relationship between gender (p-value=0.146), education (p-value=0.839), length of work (p-value=0.671), and leadership (p-value=0.680) with incident reported that patient safety at Idaman Hospital in Banjarbaru City. There is a relationship between perception and motivation with the reported of patient safety incidents in the inpatient room of RSD Idaman Banjarbaru City with a p-value of 0.002.Perception and motivation can be increased by having co-workers support in reported about patient safety incidents by not given punishment to nurses and not carried out a culture of blaming each other. The unrelated factors of gender, education, length of service, and leadership to reported could occur due to other factors such as lack of knowledge, training, and rewards. The advice in this study The Patient Safety Team at the Hospital and management at the hospital can socialize the flow of reporting patient safety incidents and make posters for health workers, especially nurses.